2014
DOI: 10.1016/j.aquatox.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomic analyses on the gender-specific responses in mussel Mytilus galloprovincialis to tetrabromobisphenol A

Abstract: a b s t r a c tTetrabromobisphenol A (TBBPA) accounts for the largest production of brominated flame-retardants (BFRs) along the Laizhou Bay in China and is the most widely used BFR in industrial products. It can induce diverse toxicities including hepatotoxicity, nephrotoxicity, neurotoxicity and endocrine disrupting effects in mammalian and fish models. In this work, we applied iTRAQ-based proteomics to investigate the gender-specific responses in mussel Mytilus galloprovincialis to TBBPA. Thirty-one protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…As a flavoprotein, NADH dehydrogenase processes iron-sulfur centers and is involved in production of reactive oxygen species in mitochondria [30]. Peptidylprolyl isomerase A is a known protein recognized as the marker of apoptosis that is also related to oxidative stress [31]. Therefore, the significant up-regulation of manganese superoxide dismutase, NADH dehydrogenase and peptidylprolyl isomerase A indicated the clear oxidative stress and consequent apoptosis induced by Cd in D-shape larval mussels.…”
Section: Resultsmentioning
confidence: 99%
“…As a flavoprotein, NADH dehydrogenase processes iron-sulfur centers and is involved in production of reactive oxygen species in mitochondria [30]. Peptidylprolyl isomerase A is a known protein recognized as the marker of apoptosis that is also related to oxidative stress [31]. Therefore, the significant up-regulation of manganese superoxide dismutase, NADH dehydrogenase and peptidylprolyl isomerase A indicated the clear oxidative stress and consequent apoptosis induced by Cd in D-shape larval mussels.…”
Section: Resultsmentioning
confidence: 99%
“…As a flavoprotein, NADH dehydrogenase contains iron-sulfur centers and is involved in production of reactive oxygen species in mitochondria [29]. These two proteins, profilin and NADH dehydrogenase, are known to be related to oxidative stress [29,30]. Therefore, the alteration of profilin and NADH dehydrogenase confirmed the oxidative stress induced by Cd in juvenile mussels.…”
Section: Tablementioning
confidence: 99%
“…The downregulation of this protein confirmed the immune stress induced by Cd in juvenile mussels, as marked by the down-regulated apextrin-like protein. Peptidylprolyl isomerase A, sorting nexin 6 and collagen alpha-6(VI) chain isoform X3 are known proteins recognized as the markers of apoptosis [30,34,35]. The alterations of these three proteins suggested that Cd exposure caused apoptosis in juvenile mussels.…”
Section: Tablementioning
confidence: 99%
“…Results indicated that mRNA expression levels of PO and CAT did not correlate with enzyme activities. The disparity between mRNA and corresponding protein expressions was not surprising as mRNA expression may not be consistent with the corresponding protein expression because of post‐transcriptional and post‐translational modifications (Ji, Wu, Wei & Zhao ).…”
Section: Discussionmentioning
confidence: 99%